Analysis of spreading dynamics of virus in wireless sensor networks - Xiao-juan LUO; Yu ZHU; Ru HUANG (物联网学报)
For virus propagation in wireless sensor networks,based on the epidemic theory,a virus propagation model with immune mechanism was proposed.Numerical calculations and experimental results show that when a small number of network nodes are added with immune mechanism,the virus propagation rate can be effectively reduced and the anti-virus capability of the network can be improved.At the same time,communication radius,transfer probability and node density of nodes have great influence on the propagation of sensor network virus.Dynamic adjustment of these parameters can make the whole network performance balance.